2022
DOI: 10.1039/d2ta02239g
|View full text |Cite
|
Sign up to set email alerts
|

Self-healable dynamic poly(urea-urethane) gel electrolyte for lithium batteries

Abstract: Hindered urea bonds are introduced as self-healing units in a polymer electrolyte for Li-metal batteries. Differently from standard commercial separators, the poly(urea-urethane) system works for hundreds of cycles after several damage/healing steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…[10][11][12] For example, self-healing materials and coatings gained focus on preventing physical and chemical damage and achieving sustainability, lower environmental impact over the lifetime, and better acceptability. [13][14][15][16] As lithium-metal batteries are maturing with time, the clock ticks not only on the improvement of existing Li-ion cells but also beyond Li-ion batteries technologies, keeping in mind that the former poses issues like stability, limited Li reserves, and recycling. [17][18][19][20] Alternatives like sodium-, potassium-, or magnesium-based batteries, just to name a few, have been actively studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] For example, self-healing materials and coatings gained focus on preventing physical and chemical damage and achieving sustainability, lower environmental impact over the lifetime, and better acceptability. [13][14][15][16] As lithium-metal batteries are maturing with time, the clock ticks not only on the improvement of existing Li-ion cells but also beyond Li-ion batteries technologies, keeping in mind that the former poses issues like stability, limited Li reserves, and recycling. [17][18][19][20] Alternatives like sodium-, potassium-, or magnesium-based batteries, just to name a few, have been actively studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the design of new solid electrolytes, a large number of studies are also being dedicated to the understanding of the long cycling cells failure via interfacial studies and thus engineering interfaces for beneficial solid electrolyte interphase (SEI) species either by surface treatments and computational predictions [10–12] . For example, self‐healing materials and coatings gained focus on preventing physical and chemical damage and achieving sustainability, lower environmental impact over the lifetime, and better acceptability [13–16] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Bella et al reported producing a self-healable crosslinked poly(urea-urethane) network by using polyethylene glycol 2000. 9 And Zhang et al successfully designed a chitosan-based dual-network self-healing hydrogel formed via ionic hydrogen bonding and ionic crosslinking. 11 In particular, interactions between molecules play a big role in dening the molecular order of organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, hydrogen and other non-covalent interactions make supramolecular aggregates of organic molecules, which are used in various applications such as optoelectronic devices, 1,2 energy storage devices, [3][4][5][6] tissue engineering, 7 injectable delivery systems, 8 self-healing materials and hydrogels suitable for use as electrolytes, and articial skin. [9][10][11] Bella et al reported producing a self-healable crosslinked poly(urea-urethane) network by using polyethylene glycol 2000. 9 And Zhang et al successfully designed a chitosan-based dual-network self-healing hydrogel formed via ionic hydrogen bonding and ionic crosslinking.…”
Section: Introductionmentioning
confidence: 99%